What Makes Korean Cuisine Favoured? Discovering The Elements Affecting Malaysia’s Younger Generations Preferences - Apriyanto, Yusup; Zulkifali, Wan Ahmad Hasni Wan; Muhammad Ramly, Alina Shuhaida; Sharif, Mohd Shazali Md; Hastuti Nurhayati; Harja, Oktomi (Politeknik Pariwisata Lombok, 2025)
Introduction: The growing popularity of Korean cuisine among Malaysia's younger generation, driven by the Hallyu Wave raises concerns about overshadowing traditional Malaysian cuisine. This study examines factors behind this trend, emphasizing the critical role of preserving Malaysia's culinary heritage as a cornerstone of national identity and cultural preservation.Methodology: Qualitative research was conducted through semi-structured interviews with eleven (11) informants aged eleven to twenty-six (11-26) at UiTM Puncak Alam. Thematic has been employed to analyse the data. Findings: This study revealed four (4) key themes including; Media Influences, Social Influences, Curiosity, and Taste, which trigger the younger generation to consume Korean Food. The study elucidates how social media platforms influence culinary preferences, driven by curiosity and social influences. Additionally, the appeal of Korean cuisine's taste, particularly its spiciness, resonates with Malaysian palates. Conclusion: Understanding the multifaceted influences on culinary preferences can guide efforts to preserve Malaysia's traditional cuisine while acknowledging the global appeal of Korean food among younger generations. However, this study is limited to exploring factors affecting the younger demographic and cannot be generalized to a broader population. Future research is recommended to validate these findings using a statistical analysis, providing a more comprehensive understanding of the dynamics shaping culinary preferences in Malaysia.